Pharmaceutical care issues of patients with rheumatoid arthritis : from hospital to community / [edited by] Louise Grech, Alan Lau - Grech, Louise
This book presents concise, comprehensive summaries of topics necessary to understand rheumatoid arthritis (RA) management, aligned with patient needs, as a reference suitable for practitioners and students of all levels.